Bonding, Bridging, and Linking Social Capital in the Construction of Religious Moderation: A Case Study an Indonesian Islamic University - Adlan Fauzi Lubis; Busahdiar, Busahdiar; Lubis, Siti Hawa; Muthohirin, Nafik; Sulthani, Dinil Abrar; Syahputra, Hardipa Iman (Universitas Muhammadiyah Malang, 2025)
This study aims to analyze the perspectives on social capital in fostering religious moderation among students, particularly in the Faculty of Islamic Studies at Muhammadiyah University of Jakarta. This study employs a qualitative, descriptive-analytical approach with a case study method, involving 12 students from the Islamic Religious Education Study Program in semesters 2–6 as research subjects, selected through purposive sampling. Data were obtained through in-depth interviews, observations, and review of supporting documents, both primary and secondary. The results of the study indicate that social capital has a significant role in internalizing the values of moderation among various students. Students who have extensive social networks, mutual trust, and active involvement in student organizations tend to exhibit a more open, inclusive, and tolerant attitude towards religion. Factors that influence the formation of students’ social capital include: (1) the multicultural social environment of the campus, (2) involvement in student organizations, (3) the role of lecturers and educational policy institutions, and (4) personal experiences and family background. These four factors contribute to the formation of students’ moderate character in religion and social interactions.